Aortic Stiffness is Associated with Cardiac Function and Cerebral Blood Flow Pulsatility in Type2 Diabetes Mellitus (International Journal of Physiology, 2019)
IntroductionCentral hemodynamics has an important role in maintaining appropriate cerebral and other end-organ perfusion and is altered in type2DM. Arterial stiffening is an early phenomenon in patients with type2DM, affecting cardiac function by increasing the cardiac afterload and reducing diastolic coronary artery perfusion, also involving small vessel disease in the brain and subsequent hypoperfusion.Aims and ObjectivesThe aim of present study was to determine whether aortic stiffness affects cardiac function and whether central elastic artery stiffness was associated with cerebral blood flow pulsatility and subsequent, cerebral perfusion in type 2 DM patients.Materials and MethodFifty six patients with type2DM and 60 age-matched healthy volunteers were enrolled. Aortic PWV was measured using non-invasive cardiovascular risk analysis system (Periscope). Cerebral blood flow was measured by using Trans-Cranial Doppler.ResultsCFPWV of diabetic group showed significantly higher mean values (Group 1=931.00±215.98cm/s Group 2=1241±152.03cm/s) than control subjects (758±151.82). CFPWV was significantly (p value